A Case of Peritoneal Dialysis-Related Peritonitis Caused by Ewingella americana. (18th February 2022) - Abrantes, Catarina; Freitas, Joana; Silva, Tânia; Marques da Silva, Luís; Carvalho, Maria João; Rodrigues, Anabela; Cabrita, António
Abstract : Peritoneal dialysis (PD)-related peritonitis is a frequent complication. PD units should be aware of all possible pathogens and share their experience about prevention and optimal management. Uncommon bacteria, a special group with crescent incidence in PD practice, may require singular considerations. A case of peritonitis due to Ewingella americana, a rare human pathogen, is reported, with a favorable outcome. To date, only three other cases have been described in the literature. New evidence is necessary for a better understanding of this pathogen and its consequences in PD modality.